The therapeutic potential of gelsolin in attenuating cytokine storm, ARDS, and ALI in severe COVID-19 - Zhi, Juan; Zhao, Kai-Xuan; Liu, Ju-Hui; Yang, Dong; Deng, Xiao-Ming; Xu, Jin; Zhang, Haoyue (Frontiers in Pharmacology, 2024)
Severe COVID-19 cases often progress to life-threatening conditions such as acute respiratory distress syndrome (ARDS), sepsis, and multiple organ dysfunction syndrome (MODS). Gelsolin (GSN), an actin-binding protein with anti-inflammatory and immunomodulatory properties, is a promising therapeutic target for severe COVID-19. Plasma GSN levels are significantly decreased in critical illnesses, including COVID-19, correlating with dysregulated immune responses and poor outcomes. GSN supplementation may mitigate acute lung injury, ARDS, and sepsis, which share pathophysiological features with severe COVID-19, by scavenging actin, modulating cytokine production, enhancing macrophage phagocytosis, and stabilizing the alveolar-capillary barrier. Preliminary data indicate that recombinant human plasma GSN improves oxygenation and lung function in severe COVID-19 patients with ARDS. Although further research is needed to optimize GSN therapy, current evidence supports its potential to mitigate severe consequences of COVID-19 and improve patient outcomes. This review provides a comprehensive analysis of the biological characteristics, mechanisms, and therapeutic value of GSN in severe COVID-19.